O processo formativo do estágio supervisionado em gestão e coordenação escolar: Um estudo na Escola Estadual de Ensino Médio Prof.ª Florentina Damasceno, Santa Luzia do Pará-PA - OLIVEIRA, Ana Claudia Sobrinho de (2023)
The present work sought to analyze and reflect on the experiences of the Supervised Internship in School Management and Coordination at the State High School Prof.ª Florentina Damasceno, understanding the internship as a formative process within the attributions that the pedagogue will exercise in his field of action. The study was developed using a qualitative approach, allowing to reach in depth the interconnections about the object of study and its relations with the subjects that build the phenomena involved. In order to carry out the analysis, a bibliographical survey was carried out on the discussions of School Management and Coordination, in addition to documentary research to deepen the data of the school documents. The research techniques used were participant observation and, as instruments for data generation, the field diary and open interviews. The supervised internship is an important curricular component in the training process of undergraduate students, as it allows these interns to enter the professional field of action, understanding and analyzing the demands and professional attributions to be subordinated. In this sense, the study showed the reality of the Escola Estadual de Ensino Médio Prof. It became evident how challenging it is to be in coordination and in School Management, since there are many situations in which these professionals intervene. The school needs a collective and democratic participation, involving both Management, Pedagogical Coordination, Teachers, Students, employees in general as well as the entire school community.